ANALISIS AKUNTANSI PENGHIMPUNAN DANA DENGAN PRINSIP WADIAH DAN MUDHARABAH DI PERBANKAN SYARIAH - Indria Widyastuti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
According to the provisions in the legislation that allowed only bank to mobilize funds from the public directly. In the Islamic Bank of community fund raising done by Wadiah and Mudharabah principle names without distinguishing the product concerned . That must be considered is the Islamic principles in raising funds as strongly associated with the reward that will be given to the owner of the funds or investors . Whatever the name of the product if the collection of funds using the mudharabah principle , then the owner will get profit-sharing funds . Instead owner wadiah funds in principle not be rewarded unless Islamic banks provide in the form of bonuses at the discretion of the Islamic banks and not agreed in advance . In this study analyzed the principle used in the raising of funds by Islamic banks deposits and principles of wadiah and mudharabah principles and applications of each of these principles. Keywords : raising funds , wadiah, mudharabah, Islamic banks